Inhibitory Effect of Punicalagin on Inflammatory and Angiogenic Activation of Human Umbilical Vein Endothelial Cells - Wei Liu; Yanghui Ou; Yumeng Yang; Xuemei Zhang; Liqi Huang; Xiaohua Wang; Buling Wu; Buling Wu; Mingcheng Huang (Frontiers Media S.A., 2021)
Punicalagin, a major ellagitannin isolated from pomegranate, is proved to have various pharmacological activities with an undefined therapy mechanism. The objective of this research was to demonstrate the effect of punicalagin on anti-inflammatory and angiogenic activation in human umbilical vein endothelial cells (HUVECs) and their potential mechanisms. Endothelial-leukocyte adhesion assay was applied to evaluate primary cultures of HUVECs activation following tumor necrosis factor alpha (TNF-α) treatment. The endothelial cell proliferation, migration, permeability and tube formation were assessed by EdU assay, wound migration assay, trans-endothelial electrical resistances (TEER) assay, and capillary-like tube formation assay, respectively. In addition, the expression of relevant proteins was assessed using Western blot analysis. We confirmed that punicalagin could reduce the adhesion of human monocyte cells to HUVECs in vitro and in vivo. Further, punicalagin decreased the expression of mRNA and proteins of ICAM-1 and VCAM-1 in HUVECs. Moreover, punicalagin inhibited permeability, proliferation, migration, and tube formation in VEGF-induced HUVECs, suppressed IKK-mediated activation of NF-κB signaling in TNF-α-induced endothelial cells, and inhibited vascular endothelial growth factor receptor 2 (VEGFR2) activation and downstream p-PAK1. Our findings indicated that punicalagin might have a protective effect on HUVECs activation, which suggested that punicalagin functions through an endothelial mediated mechanism for treating various disorders such as, cancer, rheumatoid arthritis, and cardiovascular disease.